The influence of vitamin E supplementation on yeast fermentation. Issue 2 (27th April 2016) - Zhang, Shuang; Qin, Xin; Lu, He; Wan, Min; Zhu, Yu
Abstract : Ethanol is a well‐known toxic metabolite of yeast, affecting cell growth, and it is a major factor responsible for reduced ethanol production. Therefore, yeast strains that can withstand high ethanol concentrations are highly desirable. The effects of vitamin E supplementation and enhanced cell membrane fluidity in ethanol fermentations were studied. The results showed that ethanol tolerance was significantly improved by vitamin E supplementation, which correlated with the increased level of polyunsaturated fatty acids. The data showed that, after 0.1 g L −1 vitamin E was added to the highest ethanol concentration, one could attain 118.7 g L −1, in contrast to 106.4 g L −1 . The experimental results indicated that the increase in vitamin E suppressed unsaturated fatty acid oxidation, resulting in enhanced ethanol tolerance and increased production yield. Copyright © 2016 The Institute of Brewing & Distilling